Leukocyte trafficking-associated vascular adhesion protein 1 is expressed and functionally active in atherosclerotic plaques - Silvola JMU; Virtanen H; Siitonen R; Hellberg S; Liljenback H; Metsala O; Stahle M; Saanijoki T; Kakela M; Hakovirta H; Yla-Herttuala S; Saukko P; et al. (NATURE PUBLISHING GROUP, 2025)
Given the important role of inflammation and the potential association of the leukocyte trafficking-associated adhesion molecule vascular adhesion protein 1 (VAP-1) with atherosclerosis, this study examined whether functional VAP-1 is expressed in atherosclerotic lesions and, if so, whether it could be targeted by positron emission tomography (PET). First, immunohistochemistry revealed that VAP-1 localized to endothelial cells of intra-plaque neovessels in human carotid endarterectomy samples from patients with recent ischemic symptoms. In low-density lipoprotein receptor-deficient mice expressing only apolipoprotein B100 (LDLR-/- ApoB(100/100)), VAP-1 was expressed on endothelial cells lining inflamed atherosclerotic lesions; normal vessel walls in aortas of C57BL/6N control mice were VAP-1-negative. Second, we discovered that the focal uptake of VAP-1 targeting sialic acid-binding immunoglobulin-like lectin 9 based PET tracer [Ga-68]DOTA-Siglec-9 in atherosclerotic plaques was associated with the density of activated macrophages (r = 0.58, P = 0.022). As a final point, we found that the inhibition of VAP-1 activity with small molecule LJP1586 decreased the density of macrophages in inflamed atherosclerotic plaques in mice. Our results suggest for the first time VAP-1 as a potential imaging target for inflamed atherosclerotic plaques, and corroborate VAP-1 inhibition as a therapeutic approach in the treatment of atherosclerosis.